Influence of surface sealant on the translucency of composite resin: effect of immersion time and immersion media - Garcia, Patricia Petromilli Nordi Sasso [UNESP]; Rodrigues Neto, Elídio [UNESP]; Santos, Patrícia Aleixo dos; Campos, Juliana Alvares Duarte Bonini [UNESP]; Dibb, Regina Guenka Palma (ABM, ABC, ABPol, 2008)
This study evaluated the effect of surface sealant on the translucency of composite resin immersed in different solutions. The study involved the following materials: Charisma, Fortify and coffee, Coca-Cola®, tea and artificial saliva as solutions. Sixty-four specimens (n = 8) were manufactured and immersed in artificial saliva at 37 ± 1 °C. Samples were immersed in the solutions for three times a day and re-immersed in artificial saliva until the translucency readings. The measurements were carried out at nine times: T1 - 24 hours after specimen preparation, T2 - 24 hours after immersion in the solutions, T3 - 48 hours and T4 to T9 - 7, 14, 21, 30, 60 and 90 days, respectively, after immersion. The translucency values were measured using a JOUAN device. The results were subjected to ANOVA and Tukey's test at 5%. The surface sealant was not able to protect the composite resin against staining, the coffee showed the strongest staining action, followed by tea and regarding immersion time, a significant alteration was noted in the translucency of composite resin after 21 days.
Keywords: translucency; surface sealant; composite resin